The Most Influential Educational Theories and Philosophical Movements Shaping Chinese Language Learning in The 21st Century - Ani Kariyati; M Zaim (Jurnal Ilmiah Pendidikan Scholastic, 2023)
In terms of exploring educational theories, it is very important as well as philosophical movements which have had quite a big impact on learning Mandarin in the 21st century. As the world becomes more connected, the need for effective Mandarin language acquisition is more important than ever. By studying major theories and philosophies, educators can gain insight into innovative approaches in teaching and learning Mandarin. The problem faced by teachers of Mandarin as a foreign language is a lack of understanding of educational theories and philosophical movements that greatly influence the learning of Mandarin in the 21st Century. This will have an impact on the difficulty of achieving language acquisition by students. Literature and reference searches were carried out to solve this problem. Here the author explores articles that examine and discuss the findings conceptually, the implications of educational theories and philosophical movements which have been very influential in the formation of Mandarin language learning. in the 21st century. Innovation and renewal are also a need for Mandarin language learners. Apart from that, it will challenge Mandarin language teachers to organize teaching materials in the concept of educational theory accompanied by philosophical movements for learning Mandarin in the 21st century.